Method for producing spherical particulate material

The method of granulating and spheroidizing inorganic particles addresses the challenge of controlling particle size and distribution in spherical materials, achieving high purity and efficient production without waste, suitable for semiconductor encapsulation resins.

JP7620409B2Active Publication Date: 2025-01-23ADMATECHS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020161511
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-25
Publication Date
2025-01-23
Estimated Expiration
2040-09-25

AI Technical Summary

Technical Problem

Existing methods for producing spherical particle materials from inorganic materials struggle with controlling particle size and achieving sharp particle size distributions, leading to inefficiencies and impurities, especially when high purity is required for applications like semiconductor encapsulation resins.

Method used

A method involving granulation of raw material particles with a D50 of 5 μm or less to form granules, followed by a spheroidization process to produce spherical particles with controlled particle size and distribution, eliminating the need for sieving and reducing impurities.

Benefits of technology

Enables the production of spherical particle materials with desired particle sizes and distributions without waste, maintaining high purity and sphericity, enhancing fluidity and reducing impurities like Na, U, and Th contents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620409000007
    Figure 0007620409000007
  • Figure 0007620409000008
    Figure 0007620409000008
  • Figure 0007620409000009
    Figure 0007620409000009
Patent Text Reader

Abstract

To provide a manufacturing method for a spherical particle material facilitating controlling a particle size distribution.SOLUTION: A manufacturing method for a spherical particle material includes: a granulation process of granulating a raw material particle material comprising an inorganic material with D50 of 5 μm or less, and forming a granular body; and a spheroidizing process of heating and melting the granular body and forming a spherical particle material with D50 larger than that of the raw material particle material. As for a basic method for manufacturing a spherical particle material having a required particle size distribution, a melting method is adopted, and a granular body is used for manufacturing the spherical particle material having a required particle size distribution by the melting method.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a spherical particulate material formed from an inorganic material, and more particularly to a method for producing a spherical particulate material in which particle size can be easily controlled. [Background technology]

[0002] Conventional methods for producing spherical particulate material formed from inorganic materials include a method (melting method) in which particulate material made of an inorganic material is fed into a flame formed by burning combustible gas using a powder feeder or the like, heated and melted, and rapidly cooled to continuously produce spherical particulate material, and a method (VMC method) in which, when the inorganic material is a metal oxide, a particulate material made of that metal is produced, and the particulate material is fed into an oxidizing atmosphere and deflagrated to continuously produce spherical particulate material.

[0003] However, when used as a filler for semiconductor sealing resin, etc., spherical particulate materials with extremely high purity may be required. In such cases, it is desirable to manufacture the spherical particulate materials by adopting the VMC method, which uses metals that are easy to purify as raw materials.

[0004] However, since the VMC method does not necessarily allow for the production of spherical particulate material with an arbitrary particle size, there are cases where a spherical particulate material with a required particle size cannot be obtained.

[0005] On the other hand, in the melting method, the particle size of the spherical particulate material produced can be changed depending on the particle size of the particulate material before melting. Therefore, when it is desired to obtain a spherical particulate material with a desired particle size, the particulate material as the raw material before melting is adjusted by crushing or the like, but since the particle size distribution shape becomes broad, it is not always possible to obtain a particulate material with a sharp particle size distribution shape and the required particle size, and waste occurs when the particle size distribution is adjusted by sieving or the like. In addition, the crushed particulate material as the raw material is in a crushed shape, has poor fluidity, and powder supply cannot be performed continuously, so stable production is sometimes not possible.

[0006] Furthermore, impurities from the grinding media or the grinding environment can be mixed in during grinding, which limits how much purity can be improved in the spherical particle material produced. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2012-020900 A Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention has been completed in view of the above circumstances, and an object of the present invention is to provide a method for producing a spherical particulate material which allows easier control of particle size and particle size distribution than conventional methods. [Means for solving the problem]

[0009] In order to solve the above problems, the present inventors have conducted extensive research. First, it was decided to adopt a melting method as a basic method for producing a spherical particle material having the required particle size and particle size distribution. It was found that in order to produce a spherical particle material having the required particle size and particle size distribution by the melting method, it is necessary to accurately control the particle size distribution of the raw material used in the melting method. For this purpose, it was found to be effective to use granules obtained by granulating raw particle material having a smaller particle size than the target spherical particle material to obtain the required particle size distribution.

[0010] The inventors discovered that it is possible to produce spherical particulate material having a particle size distribution corresponding to that of the granules by producing the spherical particulate material from the granules by a melting method, and thus completed the present invention. In other words, since the raw material particle material having a small particle size is granulated to obtain the required particle size distribution, there is no need to carry out sieving or the like, and this is a method for producing spherical particulate material from the raw material without waste.

[0011] (1) The method for producing a spherical particulate material of the present invention, which solves the above problems, includes a granulation step in which a raw particulate material made of an inorganic material with a D50 of 5 μm or less is granulated to form a granule, and a spheronization step in which the granule is heated and melted to form a spherical particulate material with a D50 larger than that of the raw particulate material. In this specification, "D50" refers to the particle size of the particle at the 50% position on a volume basis when the particles are arranged from the smallest particle size. Similarly, "D10" and "D90" refer to the particle size of the particle at the 10% and 90% positions from the smallest particle size. Effect of the Invention

[0012] The method for producing a spherical particulate material of the present invention includes a step of granulating particles having a particle size smaller than that of the desired spherical particulate material, which makes it possible to produce a spherical particulate material having the desired particle size distribution from the raw particle material without waste. [Brief description of the drawings]

[0013] [Figure 1] 2 is a SEM photograph of the granules of Samples 1-1 to 1-5 produced in the examples. [Diagram 2] 1 shows SEM photographs of spherical particle materials produced under conditions 1 to 3 in examples and a comparative example. [Diagram 3] FIG. 1 is a graph showing the viscosity versus shear rate of the spherical particle material produced in the examples under condition 1 and the resin composition of the comparative example under condition 3. [Figure 4] 3 is a SEM photograph of the granules of Samples 2-1 to 2-5 produced in the examples. [Diagram 5] 1 shows SEM photographs of a spherical particle material produced under condition 4 in an embodiment and a comparative example under condition 5. [Figure 6] FIG. 13 is a graph showing the viscosity versus shear rate of the spherical particle material produced in the examples under condition 4 and the resin composition of the comparative example under condition 5. [Figure 7] 3 is a SEM photograph of the granules of Samples 3-1 to 3-3 produced in the examples. [Figure 8] 4 shows SEM photographs of spherical particle materials produced under conditions 6 to 8 in the examples and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The method for producing a spherical particulate material of the present invention will be described in detail below based on the embodiment. The method for producing a spherical particulate material of the present embodiment is a method for producing a spherical particulate material made of an inorganic material. The inorganic material constituting the spherical particulate material is not particularly limited, but examples include a metal oxide, such as alumina or silica, as the main component. In particular, it is preferable that the material is made of alumina or that alumina is the main component. The term "main component" means that the material contains 50% or more by mass of the main component based on the total mass, and preferably contains 60% or more by mass, 70% or more by mass, 80% or more by mass, 90% or more by mass, or 95% or more by mass of the main component. It is also possible to determine whether each individual spherical particulate material is the main component.

[0015] The spherical particulate material of the present embodiment can be used as a filler for forming a resin composition by dispersing it in a resin material. In particular, it can be used as a filler for a resin composition for electronic materials. In particular, by adopting alumina as an inorganic material and using it as a filler for a resin composition, it is expected to be used as a thermally conductive material (TIM) with very high performance due to the excellent thermal conductivity of alumina.

[0016] When applied to fillers for electronic materials, the Na content is preferably 5 ppm or less from the viewpoint of ensuring insulation reliability or stabilizing reactivity with resins. Furthermore, particularly when used in a portion adjacent to an IC of a semiconductor memory, in addition to the above, it is preferable that the amount of α-rays generated is small, so that the spherical particle material preferably contains U and Th each at 5 ppb or less, and more preferably the total amount of U and Th is 5 ppb or less.

[0017] The sphericity of the spherical particle material to be produced is not particularly limited, but can be 0.8 or more, 0.9 or more, 0.95 or more, 0.99 or more, etc. The sphericity is measured by taking a photograph with an SEM, and using the area and perimeter of the observed particles, (sphericity) = {4π × (area) ÷ (perimeter)}2 The closer to 1, the closer to a perfect sphere. Specifically, the average value measured for 100 particles using image analysis software (Asahi Kasei Engineering Corporation: A-zo-kun) is used.

[0018] The particle size of the spherical particulate material produced by the method for producing a spherical particulate material of this embodiment is not particularly limited, but the lower limit is preferably about 1 μm, 2 μm, 3 μm, or 5 μm, and the upper limit is preferably about 50 μm, 70 μm, 100 μm, or 150 μm. These upper and lower limit values ​​can be combined in any desired manner.

[0019] The method for producing a spherical particle material according to this embodiment includes a granulation step, a spheronization step, and other steps that may be adopted as necessary.

[0020] The granulation process is a process in which the raw material particles are granulated to produce granules. The granules produced preferably have a high sphericity, for example, 0.8 or more, 0.9 or more, or 0.95 or more.

[0021] The raw particle material also preferably has a high sphericity, for example, 0.8 or more, 0.9 or more, 0.95 or more, etc. The particle size of the raw particle material is not particularly limited except that it is smaller than the particle size of the spherical particle material to be finally produced and the average particle size (D50) is 5 μm or less, but preferred upper limits of D50 include 0.1 μm, 0.3 μm, 1 μm, and 3 μm.

[0022] A preferred range for the D50 of the raw particle material in relation to the D50 of the spherical particle material is preferably 10 times or more, more preferably 15 times or more, and even more preferably 20 times or more, of the D50 of the raw particle material.

[0023] The raw particle material can be made of a material that constitutes a spherical particle material. For example, it is preferable to make it of alumina or silica. The raw particle material may have a single composition or may be a mixture of different compositions. The raw particle material may be one whose particle size is controlled simply by pulverization, one produced by a melting method or VMC method, or a combination of these methods, or one whose particle size is controlled by classification.

[0024] The pulverization method is not particularly limited, but it is preferable to adopt a method such as a jet mill to prevent impurities from being mixed in. Pulverization can also be applied to particulate materials produced by the melting method or VMC method described below to control the particle size distribution.

[0025] In the melting method, the particulate material is put into a high-temperature atmosphere to melt it, and then quenched to form particles. In the molten state, the material becomes spherical due to surface tension, and by quenching it in that state, a particulate material with high sphericity can be obtained.

[0026] The VMC method is a method for producing metal oxides, in which metal particle material composed of the metals contained in the metal oxide is combusted (deflagrated) in a high-temperature oxidizing atmosphere to produce the metal oxide, and then rapidly cooled to obtain a particle material with high sphericality. In particular, when the metal particle material is aluminum, it generates very high temperatures and oxidizes, so the generated metal oxide (alumina) vaporizes once, and when the gas is rapidly cooled in a dilute state, it becomes spherical fine particles of 5 μm or less. Therefore, the VMC method is preferable because the fine particles can be obtained without pulverization, and because the fine particles have a low melting point, granules containing them are easy to heat and melt later, and therefore it is easy to obtain ones with high sphericity.

[0027] Furthermore, the VMC method uses metals that are easy to obtain high purity materials as raw materials, and is therefore a method that can easily obtain particulate materials with controlled impurity contents. In particular, the metal particulate material preferably has a Na content of 5 ppm or less. Furthermore, it is preferable that the U and Th contents are each 5 ppb or less, and more preferably that the total amount of U and Th is 5 ppb or less.

[0028] The method of granulation in the granulation step is not particularly limited, but examples include a spray method in which a slurry composition in which raw material particles are dispersed in a dispersion medium is sprayed and dried, a disk method in which a slurry composition is supplied to a rotating disk and the slurry that comes into contact with the disk is sprayed and dried by centrifugal force, an agitation granulation method, a fluidized bed granulation method, etc. In particular, the spray method or disk method is preferable because the droplets of the slurry composition are sphericalized by surface tension and then dried, resulting in spherical granules, and therefore excellent fluidity can be obtained and the particle size distribution of the granules can be narrowed.

[0029] The produced granules preferably have a narrow particle size distribution. For example, D90 / D10 is preferably 10.0 or less, more preferably 5.0 or less, and even more preferably 3.0 or less.

[0030] It is preferable that the slurry composition contains a binder. The binder is preferably made of a polymeric material, and it is particularly preferable to use a binder that is oxidized and removed or decomposed and removed in the spheroidizing process described below. Examples of the binder include polyvinyl alcohol (PVA), polyvinylpyrrolidone, polyacrylic acid, carboxymethyl cellulose, and hydroxyethyl cellulose.

[0031] The concentration of the binder used is preferably as low as possible, and the preferred range varies depending on the type of binder, but for example, it is preferably about 0.1% to 2% based on the mass of the entire slurry composition. The binder can be prevented from precipitating alone in the obtained granules by adding an amount of the binder that completely dissolves in the dispersion medium. In order to completely dissolve the binder, in addition to a method of lowering the concentration of the binder, a method of thoroughly mixing the dispersion medium and the binder can also be mentioned. In particular, the dissolution of the binder can be promoted by mixing the dispersion medium and the binder before adding the raw particle material. In addition, it is preferable to improve the solubility by appropriately adjusting the pH of the dispersion medium or increasing the temperature during dissolution.

[0032] It is preferable that the binder is precipitated so as to thinly cover the surface of the raw material particle material to form the granules. If the binder is prevented from precipitating independently of the raw material particle material, the occurrence of depressions in the portions of the binder precipitated independently when the spheroidizing step described below is carried out under conditions for oxidizing and removing the binder can be suppressed, and the sphericity of the spherical particle material produced can be increased.

[0033] The spheronization process is a process in which the granules are heated and melted, and the raw material particles constituting the granules are fused together to integrate the granules. When heating, conditions that can decompose the binder can be adopted. For example, a method in which the binder is oxidized and removed by heating in an oxidizing atmosphere can be exemplified. The atmosphere for oxidizing and removing the binder can be air, air with added oxygen, oxygen, etc.

[0034] The heating conditions can be similar to those of the melting method. That is, the granules are placed in a high-temperature atmosphere to suspend the individual particles of the granules, and the granules are heated and melted in a separated state, and then rapidly cooled to convert the granules directly into a spherical particle material.

[0035] Taking the case where the spherical particle material is made of alumina as an example, the temperature at which it is heated and melted can be about 1000°C to 4000°C, and preferably about 1500°C to 3500°C.

[0036] To heat and melt the granules, a flame formed by burning a combustible gas, plasma, or the like can be used. After heating the granules, the molten granules are quenched by shifting from a high-temperature atmosphere to a low-temperature atmosphere to obtain a spherical particle material. The obtained spherical particle material can be classified and collected using a filter, a cyclone, or the like.

[0037] Other processes As other steps, surface treatment may be performed before granulating the raw material particles, or the obtained spherical particle material may be surface treated. Examples of surface treatment include reacting with a silane coupling agent or a silane compound such as a silazane. The silane coupling agent can introduce various functional groups onto the surface of the spherical particle material.

[0038] Furthermore, the produced spherical particle material can be subjected to a classification operation, for example, sieving or air classification, to produce a spherical particle material having a required particle size distribution.

[0039] Furthermore, fine inorganic particles (such as silica) having a particle size of about 1 nm to 20 nm can also be added. The amount of fine inorganic particles added can be about 0.1% to 2% based on the total mass.

[0040] The raw material particles can be washed. When the raw material particles have a small particle size, impurities contained therein can be easily removed by washing. For example, washing with pure water or acid washing with an aqueous solution containing a highly volatile acid such as hydrochloric acid can be performed alone or in combination. EXAMPLES

[0041] The method for producing the spherical particulate material of the present invention will be described in detail below with reference to examples.

[0042] (Test 1-1: Examination of granulation conditions) The following test was carried out to obtain granules with a D50 of about 3 to 10 μm. It was difficult to directly manufacture spherical particle material with this level of D50 from alumina using the VMC method. Alumina particles (D50 0.2 μm: ultra-high purity type: Admatechs: AO-902, Na content less than 1 ppm, U content less than 1 ppb, Th content less than 1 ppb) were used as the raw particle material. The Na content was analyzed using an ICP-AES manufactured by Agilent Technologies, and the U and Th contents were analyzed using an ICP-MS manufactured by Agilent Technologies. Granulation was carried out using this to manufacture granules (granulation process). A slurry composition was prepared for granulation. The slurry composition was prepared by mixing 100 parts by mass of the raw particle material with 1.0 part by mass of PVA (molecular weight Mw of approximately 100,000, PXP-18 manufactured by Nippon Vinyl Acetate & Poval, 8 wt% aqueous solution) as a binder in terms of PVA solids, and finally with ammonia water (26% by mass) so that the pH of the slurry composition was 10. Pure water was added so that the solids concentration became the concentration shown in Table 1. Here, the solids concentration is a value calculated from the mass of solids remaining when dried.

[0043] The prepared slurry composition was granulated using a nozzle type spray dryer (Nozzle type spray dryer NB-12: nozzle type RJ-50, manufactured by Okawara Kakoki Co., Ltd.). The granulation conditions were the air pressure (spray pressure) and the amount of slurry composition supplied, as shown in Table 1. The inlet temperature of the drying chamber was 150°C, and the outlet temperature was 88 to 100°C. The D50 of the obtained granules is shown in Table 1.

[0044] The recovery method is a method for recovering the granules after the granulation process. The cyclone is a classification means capable of capturing particles with a particle size of approximately 3 μm or more, while the bag filter is a classification means capable of capturing almost all particles if they are on the submicron order. SEM photographs of the granules obtained for each sample are shown in Figure 1.

[0045] [Table 1]

[0046] As is clear from Table 1, it was found that the D50 value of the granules can be controlled by changing the granulation conditions without changing the D50 of the raw particle material. As is clear from Figure 1, it was found that dense granules with high sphericity were obtained. In particular, it was found that as the D50 of the granules produced becomes larger relative to the D50 of the raw particle material, more dense granules can be obtained. In samples 1-1 to 1-5, the D50 of the granules is 20 times or more than the D50 of the raw particle material, and it was found that a preferable granule can be obtained by making the D50 of the granules at least 20 times or more than the D50 of the raw particle material.

[0047] (Test 1-2) The obtained granules (samples 1-5) were subjected to oxygen (secondary oxygen) of 14 Nm 3 / h while supplying 5Nm of propane gas (LPG) to the furnace. 3 / h oxygen (primary oxygen) 6Nm 3 The granules were melted by being suspended in oxygen (feed oxygen) as a feed gas into the flame formed by supplying the granules together with 10000 / h of oxygen and burning them. The spherical particle material obtained by quenching was then collected using a cyclone and a bag filter (spheroidization process). The temperature inside the furnace was approximately 2000°C. The feed gas supply rate was 10 Nm 3 / h, and under condition 2, 8 Nm 3 / h. For condition 3, a test sample for comparison was a commercially available crushed alumina particle ALM-43 (D50: 3.7 μm) manufactured by Sumitomo Chemical Co., Ltd., produced by the Bayer process, a common method for producing alumina, and the spheroidization process was tested under the same conditions as for condition 1. The melting conditions, the sample to be melted, and the obtained spherical particle material are shown in Table 2.

[0048] [Table 2]

[0049] As is clear from the table, the obtained spherical particle material has the same purity as the raw particle material, and it was found that by using particles produced by the VMC method, which makes it easy to improve purity, as the raw particle material, a spherical particle material with high purity can be obtained. It was found that the particle size of the spherical particle material depends on the particle size of the granules, so by changing the granulation conditions, it is possible to produce spherical particle material of any size. Specifically, the D50 of the obtained spherical particle material was 4.4 μm under condition 1 and 4.7 μm under condition 2. Since the D50 of the granules is 4.0 μm, it can be said that the particle size of the obtained spherical particle material and the granules are almost the same. In other words, it was found that if the particle size and particle size distribution are adjusted in advance by the granulation process, molten spherical particles that maintain these at the same level can be obtained by the spheronization process.

[0050] In particular, the particle size and particle size distribution of the granules are easy to control in this spraying method. It was found that it is possible to produce spherical particle materials from raw materials without waste, without the need for sieving or other procedures for granules with a very sharp particle size distribution, such as D90 / D10 being less than 3.0. The spherical particle material obtained had a high sphericity of 0.98 under condition 1 and 0.97 under condition 2, as shown in Figure 2. The raw particle material is a fine particle of 5 μm or less, and has a low melting point. This is thought to be because granules containing a large amount of this material are easy to melt by heating later, making it easier to obtain sphericity.

[0051] On the other hand, unlike the above, in the comparative example using ALM-43, it was found that even when melted under the same conditions as above, some of the powder was not completely melted and was mixed in. This resulted in a decrease in sphericity after melting.

[0052] Figure 3 shows the results of viscosity measurement using a rheometer, ARES-G2 manufactured by TA Instruments, of a spherical particle material obtained under condition 1 and a comparative example obtained under condition 3, which were each dispersed in liquid epoxy resin ZX-1059 manufactured by Tohto Kasei Co., Ltd. at 80% by volume. It was found that the liquid resin composition obtained under condition 1 had higher fluidity and lower viscosity. This was thought to be due to the extremely high sphericity obtained under condition 1.

[0053] (Test 2-1) The following test was carried out to obtain granules with a D50 of about 70 to 80 μm. It was difficult to directly manufacture spherical particle materials with this D50 from alumina using the VMC method. Granulation was carried out using two types of alumina particles with different particle sizes as raw particle materials (raw particle material A: D50 is 9.0 μm: Admatechs: normal purity type AO-509, Na content less than 1 ppm) and (raw particle material B: D50 is 0.2 μm: Admatechs: normal purity type AO-502, Na content less than 1 ppm), to produce granules (granulation process). The Na content was measured using an ICP-AES manufactured by Agilent Technologies.

[0054] A slurry composition was prepared for granulation. The composition ratio (parts by mass) of raw particle material A and raw particle material B in the slurry composition was set to the values ​​shown in Table 2. The average particle size of the slurry composition obtained by mixing raw particle material A and raw particle material B was regarded as D50 of the raw particle material. As a binder, PVA (molecular weight Mw is approximately 100,000, PXP-18 manufactured by Nippon Vinyl Acetate & Poval Co., Ltd., 8 wt% aqueous solution) was added in an amount of 1.0 part by mass in terms of PVA solid content, and pure water was added so that the solid content concentration became the value shown in Table 3, and then ammonia water (26% by mass) was added until the pH became the value shown in Table 2.

[0055] The prepared slurry composition was granulated using a disk-type spray dryer (Okawahara Kakoki Co., Ltd.: OUDT-25, disk type MC-125). The disk rotation speed, drying chamber inlet temperature, and outlet temperature as granulation conditions are shown in Table 3. The supply rate of the slurry composition was 68 kg / h.

[0056] [Table 3]

[0057] In samples 2-1 to 2-5, D50 was about 70 to 80 μm. As is clear from Table 3 and FIG. 4, by increasing the content of raw particle material B, raw particle material D50 (average particle diameter of composition) becomes smaller. It was found that the sphericity of the granules increases accordingly. In particular, if the D50 of the granules is 15 times or more the raw particle material D50 (average particle diameter of composition), the sphericity of the granules exceeds 0.90, so that excellent fluidity can be obtained and powder supply is expected to be stable in the melting process. Furthermore, as described later, the sphericity of the spherical particle material after melting becomes extremely high.

[0058] (Test 2-2) The granules of sample 2-3 were used as the test sample of the embodiment, and commercially available alumina particles (AL-420A, D50: 95 μm, manufactured by Sumitomo Chemical Co., Ltd.) manufactured by the Bayer process, a common manufacturing method for alumina, were used as the test sample of the comparative example, and tests of the spheroidization process were carried out (conditions 4 and 5). Note that AL-420A was previously sieved and adjusted so that it had the same particle size and particle size distribution shape as the granules of sample 2-3.

[0059] The conditions for the spheroidization process were oxygen (secondary oxygen) of 82 Nm 3 / h while supplying 35Nm of propane gas (LPG) to the furnace. 3 / h oxygen (primary oxygen) 82Nm 3 / h and burned to form a flame, oxygen as a feed gas (feed oxygen) 12 Nm 3 The test sample was suspended and fed at a rate of 21-23 kg / h to melt the granules, which were then rapidly cooled and the resulting spherical particle material was collected in a cyclone. The temperature inside the furnace was approximately 2300°C. The physical properties of each spherical particle material are shown in Table 4. SEM photographs of the obtained spherical particle materials are shown in Figure 5.

[0060] [Table 4]

[0061] As is clear from Table 4 and Figure 5, despite the same melting conditions, the sphericity was 0.98 in condition 4 and 0.94 in condition 5 (comparative example), and it was found that a spherical particle material with extremely high sphericity was obtained. This is thought to be because, as mentioned above, the sphericity of the granules (sample 2-3) was 0.97, and the excellent fluidity allowed for stable powder supply in the melting process.

[0062] Here, as in condition 5 (comparison example), the larger the particle diameter, the more difficult it tends to be to make it spheroidal. However, since the raw particle material under condition 4 contains fine particles of 5 μm or less, it is thought that it is easy to heat and melt, making it easier to obtain a material with high sphericity.

[0063] It was also found that this time, spherical particle material could be produced from raw materials without waste, without the need for sieving or other procedures for particles with an extremely sharp particle size distribution, such as a D90 / D10 ratio below 3.0.

[0064] Figure 6 shows the results of viscosity measurement using a rheometer for the spherical particle material obtained under condition 4 and the comparative example obtained under condition 5, which were each dispersed in liquid epoxy resin ZX-1059 manufactured by Tohto Kasei Co., Ltd. at 85% by volume. It was found that the liquid resin composition obtained under condition 4 had higher fluidity and lower viscosity. This was thought to be due to the extremely high sphericity obtained under condition 4.

[0065] Furthermore, in the examples, the Na value was as low as that of the raw material particle material. Therefore, it was found that the purity of the spherical particle material produced can be increased by increasing the purity of the raw material particle material. For example, it was found that the content of U and Th can be reduced by decreasing the content of the raw material particle material.

[0066] (Test 3-1) The following test was carried out to obtain granules with a D50 of about 20 to 30 μm. It was difficult to directly manufacture spherical particle materials with D50 of this order from alumina using the VMC method. Granulation was carried out using three types of alumina particles with different particle sizes as raw particle materials (raw particle material A: D50 is 9.0 μm: Admatechs: normal purity type AO-509, Na content less than 1 ppm), (raw particle material B: D50 is 0.2 μm: Admatechs: normal purity type AO-502, Na content less than 1 ppm), (raw particle material: D50 is 0.2 μm: ultra-high purity type: Admatechs: AO-902, Na content less than 1 ppm, U content less than 1 ppb, Th content less than 1 ppb), and granules were manufactured (granulation process). SEM photographs of the obtained granules are shown in Figure 7.

[0067] Slurry compositions were prepared for granulation. There were three types of slurry compositions: one in which raw particle material A and raw particle material B were mixed at the composition ratio (parts by mass) shown in Table 5, and one in which raw particle material B and raw particle material C were used alone. Here, the average particle size of the slurry composition in which raw particle material A and raw particle material B were mixed was considered to be the D50 of the raw particle material.

[0068] In addition, 1.0 part by mass of PVA (molecular weight Mw of approximately 100,000, PXP-18 manufactured by Nippon Vinyl Acetate & Poval, 8 wt% aqueous solution) was mixed as a sole binder, calculated as a PVA solid content. Pure water was added so that the solid content concentration became the value shown in Table 5, and then ammonia water (26 mass%) was added until the pH became the value shown in Table 5.

[0069] The prepared slurry composition was granulated using a disk-type spray dryer (Okawahara Kakoki Co., Ltd.: OUDT-25, disk type MC-125). The disk rotation speed, drying chamber inlet temperature, and outlet temperature as granulation conditions are shown in Table 5. The supply rate of the slurry composition was 35 kg / h.

[0070] [Table 5]

[0071] In samples 3-1 to 3-3, D50 was about 20 to 30 μm. As is clear from Table 5 and FIG. 7, by increasing the content of raw particle material B, raw particle material D50 (average particle diameter of composition) becomes smaller. It was confirmed that the sphericity of the granules increases accordingly. In particular, it was found that if the D50 of the granules is 20 times or more the raw particle material D50 (average particle diameter of composition), the sphericity of the granules becomes 0.95 or more.

[0072] (Test 3-2) The granulated bodies of Samples 3-1 to 3-3 were used as test samples of the embodiment, and tests of the spheronization process were carried out (Conditions 6 to 8).

[0073] The spheroidization process conditions were: oxygen (secondary oxygen) of 82 Nm 3 / h while supplying 35Nm of propane gas (LPG) to the furnace. 3 / h oxygen (primary oxygen) 82Nm 3 / h and burned to form a flame, oxygen as a feed gas (feed oxygen) 12 Nm 3 The test sample was fed in a suspended state at a rate of 40-80 kg / h to melt the granules, which were then rapidly cooled to obtain spherical particles, which were then collected in a cyclone. The temperature inside the furnace was approximately 2300°C.

[0074] The physical properties of each spherical particle material are shown in Table 6, and SEM images are shown in Figure 8.

[0075] [Table 6]

[0076] As with the other particle sizes mentioned above, the obtained spherical particle material has the same purity as the raw particle material. Therefore, it can be said that by using particles produced by the VMC method, which makes it easier to improve purity, as the raw particle material, a spherical particle material with high purity can be easily obtained.

[0077] Since the particle size of the spherical particle material depends on the particle size of the granules, it was confirmed that it is possible to produce spherical particle material of any size by changing the granulation conditions. In other words, if the particle size and particle size distribution are adjusted in advance by the granulation process, molten spherical particles can be obtained that maintain the same particle size and size distribution.

[0078] Furthermore, as shown in Table 6 and FIG. 8, it was confirmed that the spherical particle material obtained under these conditions had extremely high sphericity.

[0079] In this way, according to the present invention, it is possible to efficiently obtain spherical particle materials having extremely low Na contents as well as extremely low U and Th contents, extremely high sphericity, and any particle size and sharp particle size distribution.

Claims

1. A granulation step of granulating a raw material particle material made of an inorganic material having a D50 of 5 μm or less to form a granule; a spheronization step of heating and melting the granules to form a spherical particulate material having a larger D50 than the raw particulate material; having The sphericity of the raw particle material is 0.95 or more; The D50 of the spherical particle material is 10 times or more the D50 of the raw particle material; A method for producing a spherical particulate material, wherein the D50 of the granules is 15 times or more the D50 of the raw particulate material.

2. The granulation step is a step of granulating a slurry composition, which is a mixture of the raw particle material, a binder, and a dispersion medium, by spray drying; The method for producing a spherical particulate material according to claim 1 , wherein the spheroidizing step is carried out under conditions in which the binder can be oxidized and removed in an oxidizing atmosphere.

3. The method for producing a spherical particulate material according to claim 2 , wherein the binder in the slurry composition is completely dissolved in the dispersion medium.

4. The method for producing a spherical particulate material according to claim 2 or 3, wherein the slurry composition has a pH of 9 or more.

5. The inorganic material contains 50% or more of alumina based on the total mass, The method for producing a spherical particulate material according to any one of claims 1 to 4, wherein the raw particle material is produced by a deflagration process in which a metal particle material made of metallic aluminum is deflagrated in an oxidizing atmosphere to convert it into alumina.

6. A method for producing a spherical particulate material as described in claim 5, wherein the deflagration process includes a process for controlling the particle size of the particles obtained by deflagration by classification.

7. The metal particle material has a Na content of 5 ppm or less, The method for producing a spherical particulate material according to claim 5 or 6, wherein the spherical particulate material has a Na content of 5 ppm or less.

8. The metal particle material has a U and Th content of 5 ppb or less, The method for producing a spherical particulate material according to any one of claims 5 to 7, wherein the spherical particulate material has a U and Th content of 5 ppb or less.

9. The method for producing a spherical particulate material according to any one of claims 1 to 8, wherein the spherical particulate material has a D90 / D10 ratio of 3.0 or less.

Citation Information

Patent Citations

  • Slurry of ceramic powder and production of ceramic granule

    JP1994092714A

  • Production of ceramic granule

    JP1994234563A

  • Production of spherical inorganic particle having large particle diameter

    JP1998137574A

  • Filler-containing aqueous slurry composition

    JP2008184485A

  • Spherical alumina powder, and method of production and application thereof

    JP2012020900A